2017
DOI: 10.1007/s10103-017-2208-8
|View full text |Cite
|
Sign up to set email alerts
|

Melanogenesis inhibition in mice using a low-fluence 1064-nm Q-switched neodymium-doped yttrium aluminum garnet laser: a pilot study

Abstract: A low-fluence 1064-nm Q-switched neodymium-doped yttrium aluminum garnet laser, or laser toning, has yielded favorable outcomes in various benign pigmented disorders. However, the exact mechanism of action of laser toning has not been fully elucidated. We sought to determine the inhibitory effect of laser toning on melanogenesis and to assess how laser passes influence the outcomes. To produce perceptible pigmentation, nine HRM-2 melanin-possessing hairless mice were treated with ultraviolet (UV) B radiation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Melanogenic stimulators, including a-MSH and NGF, were also reduced. Similar results were also reported by Nam et al [16] They also reported that there is a positive correlation between number of passes and pigmentation improvement. Omi et al [17] compared ultrastructural changes after toning with QSL to q-switched ruby laser and concluded that QSL toning offered superior results with less epidermal disruption and cellular damage, thus, confirming the safety of toning with QSL.…”
Section: Laser Toningsupporting
confidence: 90%
“…Melanogenic stimulators, including a-MSH and NGF, were also reduced. Similar results were also reported by Nam et al [16] They also reported that there is a positive correlation between number of passes and pigmentation improvement. Omi et al [17] compared ultrastructural changes after toning with QSL to q-switched ruby laser and concluded that QSL toning offered superior results with less epidermal disruption and cellular damage, thus, confirming the safety of toning with QSL.…”
Section: Laser Toningsupporting
confidence: 90%
“…2 The exact mechanism by which low-fluence 1064-nm Q-switched Nd: Yag laser improves pigmentary lesions is not fully clarified; the induction of "subcellular selective photothermolysis" and the inhibition of melanogenesis, reported in mice, has been proposed as hypothesis. 3,4 Five hundred and thirty-two-nanometer Q-switched neodymiumdoped yttrium aluminum garnet (Nd:Yag) laser does not penetrate deeply into the skin and is suitable for epidermal pigmented lesion. 5 We describe a clinical case of a 16-years-old female patient who presented congenital solitary asymptomatic, polygonal, brown stain (Café-au-lait macule), measuring 8 Â 4 cm, on the zygomatic-temporal area of her right face emilate.…”
mentioning
confidence: 99%